Tiger time 2 : studentS book with eBook - Read, Carol (London : Macmillan Education, 2015)
Within each unit of the Student$1 (Bs Book are lessons that have been structured to focus on vocabulary, grammar and skills, and then building to CLIL, culture and projects. A code gives access to the Student$1 (Bs Resource Centre where a digital platform offers a wealth of extra material. Also included is an eBook version of the Student$1 (Bs Book.s
Keywords: English language -- Study and teaching (Elementary) -- Foreign speakers; English language -- Study and teaching (Elementary)